2020
DOI: 10.1111/jar.12802
|View full text |Cite
|
Sign up to set email alerts
|

The value of competitive employment: In‐depth accounts of people with intellectual disabilities

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…The summary was also presented to the participant in the member check to ensure it reflected the participant's perceptions (Voermans et al, 2021). The researcher asked questions to check the interpretation of the interview in order to deepen the understanding of the perception of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…The summary was also presented to the participant in the member check to ensure it reflected the participant's perceptions (Voermans et al, 2021). The researcher asked questions to check the interpretation of the interview in order to deepen the understanding of the perception of the participant.…”
Section: Discussionmentioning
confidence: 99%
“…from an outside perspective and provided insight into any biases influencing the analyses. The debriefer reported that the findings seemed both accurate and plausible (e.g., see Voermans et al, 2021). None of the participants responded.…”
Section: Credibilitymentioning
confidence: 98%
“…50 Open or competitive employment is an invaluable tool to build the PID’s self-esteem and social experience, and may also pay better, but has various challenges such as unstable market conditions, discrimination, and difficulty in retaining jobs. 51 Sheltered employment provides a safe workplace, but can lead to segregation, under- utilization of potential, lower wages, and poor job satisfaction. 52 With self-employment, problems such as irregular income and loss of income due to sick days are common.…”
Section: Interventionmentioning
confidence: 99%